If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 23y + -46x = 0 Reorder the terms: -46x + 23y = 0 Solving -46x + 23y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-23y' to each side of the equation. -46x + 23y + -23y = 0 + -23y Combine like terms: 23y + -23y = 0 -46x + 0 = 0 + -23y -46x = 0 + -23y Remove the zero: -46x = -23y Divide each side by '-46'. x = 0.5y Simplifying x = 0.5y
| 3p+12=99 | | -2c-36=2c+16 | | n^2-10n=23 | | 7x=56x | | 2x-12=2x+3 | | 3(x+6)+2x=10 | | -3(4y+2)-6y=-10y-22 | | 23x-46y= | | y=48.149(x)-2000000 | | 4x^2+35x+24= | | B=22.5n+27.5 | | 4.019=t-6.11 | | (13x+8)+(7x-8)=180 | | Z^3-2z^2+(-2+3i)z+1+3i=0 | | -7=10x+3 | | 5(3x+7)-1=3(5x+5)+4 | | 4x-0.08x^2=0 | | 9a-8=118 | | 7x-3x=5x+2A | | -8x-50=46 | | 4x+2(x-3)=3(x-1) | | 13=-8m+5 | | -3(x+6)-6=-12 | | -14=8x+50 | | 3-2=8-3/-3 | | 2x^2+3x^2=169 | | 5x+23(x-3)=155 | | -4=10+n | | -16=4y+8 | | -5(x+2)-2=-7 | | -14=-10-2x | | 24=h/18-16-`4 |